Characterization of Rhizosphere Bacteria in the Rice Fields of the Sawah Tambak Rice-Fish Farming System - Mahbubilllah, M Ainul; Aisyah, Neelam; Solekha, Rofiatun; Rohmah, Laila Ainur (Program Studi Pendidikan Biologi, 2024)
The Sawah Tambak Rice-Fish Farming System is a land-use practice that alternates between rice cultivation and fish farming depending on the season. During the dry season, the land is used for growing rice, while in the rainy season, it functions as a fishpond. Successful rice cultivation in this system relies on beneficial rhizosphere bacteria that interact with plant roots through biological, physical, and chemical processes. This study aims to characterize bacteria isolated from the rhizosphere of rice plants (Oryza sativa L.) in this system and evaluate their ability to produce indole-3-acetic acid (IAA) and solubilize phosphate. Bacterial colony identification was performed using the streak plate method, IAA production was measured via spectrophotometry, and phosphate solubilization was assessed using the phosphate solubilization index (PSI). The results showed diverse bacterial isolates with distinct morphological, biochemical, and physiological characteristics. Several isolates exhibited strong IAA production, with B3 reaching the highest concentration (18.29 ppm) on the sixth day. Phosphate-solubilizing bacteria (PSB) were also identified, with B4 and S5 showing the highest PSI values of 6.06 and 5.3, respectively. These findings suggest that rhizosphere bacteria in the Sawah Tambak system have the potential to enhance rice growth by improving phosphorus availability and producing plant growth hormones, contributing to sustainable and environmentally friendly rice cultivation